DEVELOPING SPEECH-RELATED COMPETENCIES IN PRIMARY SCHOOL STUDENTS - Ashurova Sojida Abdusamad qizi, (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: This article explores the importance and strategies of developing speech-related competencies in primary school students. Oral communication skills such as pronunciation, vocabulary use, sentence formation, fluency, and listening comprehension are crucial for academic success and social integration. The study examines pedagogical approaches and classroom techniques that help enhance learners’ verbal abilities in early education. It also emphasizes the role of teachers, curriculum design, and supportive environments in fostering strong speech skills among young learners.